Upper Limb Morbidity and Quality of Life After Lymph Node Sentinel Biopsy for Breast Cancer Treatment - Velloso, Fernanda Saltiel Barbosa (2009)
The second most frequent cancer type worldwide and the most frequent in women is breast cancer. Sentinel lymph node biopsy (SLNB) has become a trend in therapeutic approach nowadays, once it allows disease control with minimal surgical intervention and grants low morbidity rates. This article aims at reviewing literature on musculoskeletal impairments and quality of life among women treated through SLNB for breast cancer. Pubmed, Cochrane, Scielo and Lilacs databases were searched through the years of 1997 to 2008. Medical subject heading terms uses were breast neoplasms, sentinel lymph node biopsy, morbidity and quality of life. Seventy six articles were retrieved and 22 were selected. Results showed the most studied morbidities were sensory disorders (7% to 88% prevalence), pain (3,5% to 39%), lymphedema (0% e 22%), shoulder range of motion impairment (3% to 16%), daily living activities restriction (7,8% to 27,8%) and quality of life deterioration. After 36 months upper limb morbidities hardly seem to interfere with quality of life. Patients have mostly worried about cancer recurrence. Surgery time lapsed and instruments used for data retrieving explain variability in symptoms prevalence. Long term follow-up studies to evaluate morbidities and quality of life research on Brazilian population are missing.